Is more automation always better? An empirical study of customers' willingness to use autonomous vehicle functions. (14th February 2020) - Souka, Mohamed; Böger, Daniel; Decker, Reinhold; Stummer, Christian; Wiemann, Alisa
Sometime, many (maybe all) vehicles on our streets will drive autonomously - or at least have autonomous functions. However, in the short run, consumers' preferences regarding the automation of pivotal vehicle functions are not entirely clear. This paper accordingly investigates consumers' willingness to use three levels of automation (none, partial, and full) of potentially autonomous vehicle functions (safety, parking prediction, and remote diagnostics). The results show that consumers' willingness to use autonomous vehicle functions is generally the highest for moderately autonomous functions and that the willingness to use these functions decreases above a certain level of autonomy. This paper also finds that this effect is moderated by gender and depends on individual involvement level with respect to autonomous vehicle functions, that is, highly involved consumers are more likely to appreciate autonomous vehicle functions compared with low-involved consumers.